Tunable stress induced magnetic domain configuration in FePt thin films - Alvarez, Nadia Roxana (2015)
We present a study of the magnetic properties of chemically disordered ferromagnetic FePt films of 100 nm thickness that have been grown by sputtering with different Ar pressures (3 mTorr ≤PAr < 13 mTorr). We found that the residual stress can be controlled by the sputtering pressure, which in turn allows to tune the perpendicular magnetic anisotropy due to magnetoelastic effects. Films deposited at lower Ar pressures display an in-plane compressive stress that favors an out of plane component of the magnetization and the formation of a magnetic domain structure in the form of stripes. For higher pressures the stress is relaxed and the magnetic configuration changes to planar domains. These results show the possibility to accurately tune the initial magnetic state in films with potential applications in magnetoelectrically coupled devices.